The influence of spray droplet characteristics on the efficacy of permethrin against the diamondback moth Plutella xylostella: The effect of drop size and concentration on the potency of ulv- and ec-based residual deposits - Omar, Dzolkhifli; Matthews, Graham A.; Ford, Martyn G.; Salt, David W. (Wiley, 1991)
The effect of droplet diameter (36-274 μm) and concentration (10-400 g litre−1) of permethrin on the knockdown and mortality of 2nd-instar Plutella xylostella larvae was investigated. Larvae were placed on brussels sprout leaf discs treated with residual deposits of permethrin applied as ULV or emulsion formulations. The LD50 of permethrin decreased with droplet size at all concentrations tested. This effect could not be accounted for solely by increased drop numbers per unit area of leaf, suggesting that for both formulations transfer of permethrin to larvae is more efficient for deposits composed of small drops. The concentration of permethrin in the ULV formulation could be reduced to approach a minimum quantity of toxicant per unit area to maintain 50 per cent mortality. The approach to the minimum dose varied with drop size and drop number per unit leaf area. The ULV formulation was approximately 2.7 times more effective at killing larvae than the emulsion, presumably as a result of greater availability of toxicant and transfer to larvae.